Interfacial microstructure and corrosion behavior of ODS FeCrAl alloy in oxygen-saturated lead-bismuth eutectic at 450 °C - Yang Luo; Shengqiang Ma; Ping Lv; Yusheng Liu; Xiaoting Wang; Liangliang Lv; Jiandong Xing (Scientific Reports)
Abstract The interfacial microstructure and corrosion behavior of oxide dispersion strengthening (ODS) FeCrAl alloy with 20 wt% Cr (e.g. 20Cr ODS FeCrAl alloy) exposed to static oxygen-saturated lead-bismuth eutectic (LBE) at 450 °C for 20 h, 40 h, 60 h, 80 h and 100 h as exposure time respectively have been investigated. The results show that multilayer corrosion films of 20Cr ODS FeCrAl alloy can exist at the corrosion interface. Due to formation of protective scales, the primary corrosion mechanism of 20Cr ODS FeCrAl alloy in LBE is oxidation rather than dissolution and penetration of liquid LBE. Specially, the spinel-shaped nano-sized dense external layer without any microcracks is obviously observed. Moreover, the dense and compact scale with micron-meters, i.e. Al-rich Fe-Cr spinel, generates at interface as the middle layer to effectively defend inward diffusion of oxygen and penetration of LBE. Meanwhile, a reinforced and continuous internal layer mixed with Cr2O3 scale and the ferrite inner oxidation zone (IOZ) existing in the form of the interlocking interface between the layers and the substrate can further promote the adhesion between corrosion layers and the substrate of 20Cr ODS FeCrAl.